2021
DOI: 10.3389/fpls.2021.679659
|View full text |Cite
|
Sign up to set email alerts
|

A High-Density SNP Genetic Map Construction Using ddRAD-Seq and Mapping of Capsule Shattering Trait in Sesame

Abstract: The seed-bearing capsule of sesame shatters at harvest. This wildish trait makes the crop unsuitable for mechanized harvesting and also restricts its commercial potential by limiting the cultivation for countries that have no access to low-cost labor. Therefore, the underlying genetic basis of the capsule shattering trait is highly important in order to develop mechanization-ready varieties for sustainable sesame farming. In the present study, we generated a sesame F2 population derived from a cross between a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Additionally, Wang et al (2017) developed a genetic map with 13 linkage groups (chromosome numbers) and discovered 14 QTLs responsible for sesame resistance to charcoal rot disease. More recent results from Liang et al (2021) , Asekova et al (2021) , XU et al (2021) , and Yol et al (2021) have reported high-density genetic linkage maps of sesame using 1,354 bins, 1,662 SNPs, 424 SNPs, and 782 SNPs, respectively ( Figure 4 ). Furthermore, Li et al (2021) developed a super-dense genetic linkage map of 17 QTLs of seed coat color using 22,375 marker bins in 13 LGs ( Figure 4 ).…”
Section: Sesame Markers and Genetic Linkage Mapsmentioning
confidence: 93%
See 3 more Smart Citations
“…Additionally, Wang et al (2017) developed a genetic map with 13 linkage groups (chromosome numbers) and discovered 14 QTLs responsible for sesame resistance to charcoal rot disease. More recent results from Liang et al (2021) , Asekova et al (2021) , XU et al (2021) , and Yol et al (2021) have reported high-density genetic linkage maps of sesame using 1,354 bins, 1,662 SNPs, 424 SNPs, and 782 SNPs, respectively ( Figure 4 ). Furthermore, Li et al (2021) developed a super-dense genetic linkage map of 17 QTLs of seed coat color using 22,375 marker bins in 13 LGs ( Figure 4 ).…”
Section: Sesame Markers and Genetic Linkage Mapsmentioning
confidence: 93%
“…In Bulgaria, four sesame varieties (victoria, aida, valya, and nevena) have been developed that are suitable for mechanized farming (Myint et al, 2020). Although the shattering trait is considered to be qualitative and controlled by a single major gene (Yol et al, 2021), this topic has received less attention, and research to identify indehiscent/shattering resistant candidate genes for sesame is required. Wongyal et al (1997) aimed to develop shattering-resistant genotypes using gamma rays and ethyl methanesulfonate (EMS)induced mutations in the Kasetsart University Sesame Breeding Project in Thailand.…”
Section: Other Genes and Qtlsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the restriction-site associated DNA sequencing (RAD-seq) method was utilized to construct a high-density genetic map with 1230 markers, and several grain yield-related QTLs were identified [ 21 ]. Up to now, eight more genetic linkage maps have been constructed in sesame with SLAF-seq, RAD-seq, ddRAD-seq or GBS [ 30 , 31 , 32 , 33 ]. These genetic maps have been used to identify QTLs related to yield and yield components, seed quality, disease resistance, stress tolerance, and other traits in sesame.…”
Section: Genomicsmentioning
confidence: 99%